Evaluation of Physical Education Online Learning of Junior High School During the COVID-19 Pandemic in Cepiring, Kendal Regency - Fika, Moh. Aula; Soegiyanto, Soegiyanto; Setyawati, Heny (Journal of Physical Education and Sports, 2021)
The background of the research is the pandemic period which forced physical education (PE) in schools to carry out online learning in junior high schools throughout the Cepiring District, Kendal Regency. Method used a qualitative study with CIPP evaluation paradigm. The study was conducted in junior high schools in Cepiring sub-District, Kendal Regency. The research subjects consist of 3 physical education teacher in Cepiring sub-district, 3 Deputy Head of Curriculum junior high school curriculum assistants in Cepiring sub-district, 30 students of IX grade junior high school, and 10 parents of students. Data collected by observation, interview, and documentation. Data analysis was comprised of 4 interacting components: data collection, reduction, display, and conclusion. The result showed that contact in the form of online physical education learning materials was adapted to the online learning situation using physical education learning videos in junior high schools throughout the Cepiring sub-district. The input to physical education learning was provided by Wa, YouTube, Google Forms, and the School App, which required each teacher to create a Learning Implementation Plan. The process of learning was done online using virtual learning media. Through the evaluation of assignments and tests, students in Physical Education achieved outcomes above the Minimum Completeness Criteria established by each junior high school in Cepiring sub-District. Conclussion that online physical education learning was done effectively in junior high schools throughout Cepiring Sub-District, Kendal Regency, despite some obstacles, and should be used as evaluation material for physical education online learning in the COVID-19 pandemic.